Contemporary Mathematics for Business & Consumers, 9th Edition - Robert Brechner; Geroge Bergeman (Cengage Learning, 2019)
Invite students into a successful, interactive learning experience with Brechner/Bergeman's CONTEMPORARY MATHEMATICS FOR BUSINESS AND CONSUMERS, 9E. This unique, modular approach helps even the most uncertain students overcome math anxiety, master key mathematical concepts and understand math's business applications. A proven, step-by-step instructional model progresses through one topic at a time so readers are not intimidated or overwhelmed, while a reader-friendly design offers numerous real business examples and integrated instructional technology. Students immediately practice concepts with more than 2,000 new, revised and proven exercises in this edition. Engaging problems with interactive solutions and author-created videos that walk students through sample problems further reinforce learning and hone essential skills.